2015
DOI: 10.3390/su71013192
|View full text |Cite
|
Sign up to set email alerts
|

Declining Energy Intensity in the U.S. Agricultural Sector: Implications for Factor Substitution and Technological Change

Abstract: This study examines factor substitution and energy intensity in the U.S. agricultural sector. Not only does this study focus on the substitution possibilities between energy and non-energy factors, but it also attempts to identify the factors that determine energy intensity. For the empirical analysis, a system of share equations for capital, energy and labor is estimated to calculate the price elasticities of factor demand. The findings reveal that energy demand is more elastic than the demand for capital and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Takeshima et al [41] explored the substitution relationship between energy and labor in southern Nigeria, and found that the substitution relationship between them was beneficial to increasing farmers' income. Suh [42] found that energy-capital and energy-labor in U.S. agriculture exhibited substitutability between 2000 and 2011, with rising energy prices reducing their intensity of use and output contribution. This paper provides empirical research for studying the substitution relationships of production factors in Chinese agriculture Table 7.…”
Section: Substitution Elasticitiesmentioning
confidence: 99%
“…Takeshima et al [41] explored the substitution relationship between energy and labor in southern Nigeria, and found that the substitution relationship between them was beneficial to increasing farmers' income. Suh [42] found that energy-capital and energy-labor in U.S. agriculture exhibited substitutability between 2000 and 2011, with rising energy prices reducing their intensity of use and output contribution. This paper provides empirical research for studying the substitution relationships of production factors in Chinese agriculture Table 7.…”
Section: Substitution Elasticitiesmentioning
confidence: 99%
“…The use of labor has been replaced either by machinery and agricultural chemicals, such as fertilizers and pesticides or by purchased contract labor services [16,17]. In addition, rising energy prices have forced the sector to endure increasing energy costs under the producers' budget constraints [18], and the agricultural sector has substituted chemicals for land to intensify productivity as land becomes scarce relative to other inputs [19,20]. The composition changes in input usage were attributed to rising and volatile input prices and unproductive weather conditions, which seemed to put pressure on production costs.…”
Section: Introductionmentioning
confidence: 99%